The Benefits and Challenges of Open Educational Resources (OER) and Open Educational Practices (OEP) - Ziko Rizk (2017)
In this action research project, the benefits and challenges of using Open Educational Resources (OER) and Open Educational Practices (OEP) were examined for the CS120 Digital Literacy course at the LinnBenton Community College (LBCC) in Albany, Oregon. Two types of research data were gathered, quantitative and qualitative. The quantitative data were based on the end-of-quarter metrics for the six established CS120 course outcomes (see appendix A). The participants for the quantitative data are the students from the eighteen CS120 sections which were taught during the 2016 calendar year (winter, spring, and fall). While the ten winter and spring CS120 sections used a publisher textbook and companion website material, the eight fall CS120 sections used OER material. For the qualitative data, a student questionnaire was used (see appendix B). The participants of the qualitative data are the twenty-eight students in my two fall CS120 sections which read and signed the Student Consent Form (See appendix D). The findings of this study indicated: 1) The quantitative data, based on course outcomes, were very positive. The data revealed that all six course outcomes improved in the fall quarter and each student saved $162 on textbooks. 2) The qualitative data, based on a questionnaire, were also positive. The majority of the students stated that the OER-based course is well structured, accessible, easy to use, and the content covers all six course outcomes. One concern is that 57% of the students stated they missed having a physical textbook.